VETIVER ROOT PLANTING FOR PREVENTION AND MITIGATION OF LANDSLIDES IN DISASTER-PRONE AREAS, NGANJUK, EAST JAVA - Arie Utariani; Soni Sunarso Sulistiawan; Hamzah Hamzah; Christrijogo Soemartono Waloedjo; Kun Arifi Abbas; Belindo Wirabuana; Teuku Aswin Husain; Maulana Hanif Ibrahim; Alivery Raihanda Armando (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
Landslide is the transfer of slope-forming material in the form of rocks, debris, soil moving down or out of the slope. Geolologically, landslides are a geological phenomenon with a movement of land such as falling rocks or large lumps of land (Nandi, 2007). The majority of Nganjuk Regency, East Java, is at high risk of landslides. Reporting from Tirto.id news on February 19, 2021, there was a landslide in Ngetos Subdistrict, Nganjuk which claimed many victims. Nineteen people died, 20 were injured and 10 houses were severely damaged. Ngetos village is the largest village with the most populous population in Nganjuk. Unit of Natural Disease Support from Faculty of Medicine, Community Service Team of the Department of Anesthesiology and Reanimation Faculty of Medicine Universitas Airlangga in collaboration with the Center of Environmental Health Engineering and Disease Control (BBTKLPP) Surabaya in efforts to overcome landslide disasters that occurred in Nganjuk. Assistance provided includes medical assistance and environmental development as one of the disaster mitigation efforts. One of the mitigation measures carried out through this activity is reforestation by planting vetiver roots. Vetiver Roots are known as landslide prevention plants because their roots can reach depths soil of down to 5 meters. One of the causes of landslides is the lack of vegetation on the ground so it is prone to movement, especially if it rains heavily because there is no anchoring. Therefore, this activity is considered important to prevent repeated landslides.